2015
DOI: 10.5195/jyd.2015.422
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Character and Resiliency among Elementary School Students: An Assessment of the CARE Now Program

Abstract: Youth, especially in inner-city areas of the country, are in need of effective, outcome-based camp programs when school is not in session. Character and Resiliency Education (CARE) Now (CN) is a comprehensive in-and afterschool program designed to promote academic enrichment through positive youth development with a focus on enhancing character and resiliency. In the summer of 2013, CN was adapted to create a three-week long day camp at a high-needs elementary school in eastern Virginia. Using theoretically-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…This instrument consisted of 24 “I” statements, such as “I am good at making friends” measured on a 6-point Likert scale, with multiple inquiries about each of the seven resiliency traits. The questionnaire has demonstrated evidence of reliability (Cronbach’s alpha = 0.84) and construct validity ( 20 ).…”
Section: Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This instrument consisted of 24 “I” statements, such as “I am good at making friends” measured on a 6-point Likert scale, with multiple inquiries about each of the seven resiliency traits. The questionnaire has demonstrated evidence of reliability (Cronbach’s alpha = 0.84) and construct validity ( 20 ).…”
Section: Design and Methodsmentioning
confidence: 99%
“…According to Borus and Laffel, “The spontaneity and sense of immortality and exceptionalism that are hallmarks of the teen years are counter to effective diabetes management” ( 4 ). Using resiliency as a framework for education that positions youth to address their own needs could be helpful ( 20 ).…”
Section: Resiliencymentioning
confidence: 99%
See 1 more Smart Citation
“…The character education in the learning material needed to support the implementation of character education target can be obtained in full. [6].…”
Section: A Character Educationmentioning
confidence: 99%
“…Based on the experts' statements, it can be concluded that implementation is a series of activities from ideas that are planned and have been arranged to achieve the objectives. The plan should be performed by identifying needs, formulating vision, formulating missions, and defining programs [7]. Good planning will guide to good implementation of the character education [8].…”
Section: A Implementationmentioning
confidence: 99%